A room with a green view: the importance of nearby nature for mental health during the COVID-19 pandemic - Soga, Masashi; Evans, Maldwyn J; Tsuchiya, Kazuaki; Fukano, Yuya (Ecological applications, 2021)
The COVID-19 pandemic and its global response have resulted in unprecedented and rapid changes to most people's day-to-day lives. To slow the spread of the virus, governments have implemented the practice of physical distancing ("social distancing"), which includes isolation within the home with limited time spent outdoors. During this extraordinary time, nature around the home may play a key role in mitigating against adverse mental health outcomes due to the pandemic and the measures taken to address it. To assess whether this is the case, we conducted an online questionnaire survey (n = 3,000) in Tokyo, Japan, to quantify the association between five mental health outcomes (depression, life satisfaction, subjective happiness, self-esteem, and loneliness) and two measures of nature experiences (frequency of greenspace use and green view through windows from home). Accounting for sociodemographic and lifestyle variables, we found that the frequency of greenspace use and the existence of green window views from within the home was associated with increased levels of self-esteem, life satisfaction, and subjective happiness and decreased levels of depression, anxiety, and loneliness. Our findings suggest that a regular dose of nature can contribute to the improvement of a wide range of mental health outcomes. With the recent escalation in the prevalence of mental health disorders, and the possible negative impacts of the COVID-19 pandemic on public mental health, our findings have major implications for policy, suggesting that urban nature has great potential to be used as a "nature-based solution" for improved public health.